2002
DOI: 10.1590/s0100-204x2002000200010
|View full text |Cite
|
Sign up to set email alerts
|

Funções e ordem da razão dos nutrientes no estabelecimento de normas DRIS em laranjeira 'Valência'

Abstract: Resumo O sistema integrado de diagnose e recomendação DRIS (Diagnosis and Recommendation Integrated System) tem sido uma boa alternativa para a avaliação do estado nutricional de diversas culturas. O objetivo deste trabalho foi calcular índices DRIS mediante o uso de três métodos (Beaufils, Elwali & Gascho e Jones) de cálculo das funções das razões dos nutrientes e de dois critérios (Letzch e Nick) para a escolha da ordem da razão dos nutrientes, em pomares comerciais irrigados de laranjeira Valência . Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…However, determining whether a nutrient is potentially limiting or excessive depends of the criterion adopted, which may be an index or an absolute value higher than the average NBIm or other criteria (Wadt et al, 1998). In addition, the definition of the best nutritional diagnosis method can be established by the correlation between agricultural productivity and NBIm (Mourão Filho et al, 2002), but in this study no significant correlations were observed between productivity and NBIm in any of the methods tested. This fact can be explained by the influence of other factors on productivity because good nutritional conditions do not necessarily reflect in high yields.…”
Section: Nbim Of the Sugarcane Crops By The Dris And Cnd Methods And mentioning
confidence: 66%
See 1 more Smart Citation
“…However, determining whether a nutrient is potentially limiting or excessive depends of the criterion adopted, which may be an index or an absolute value higher than the average NBIm or other criteria (Wadt et al, 1998). In addition, the definition of the best nutritional diagnosis method can be established by the correlation between agricultural productivity and NBIm (Mourão Filho et al, 2002), but in this study no significant correlations were observed between productivity and NBIm in any of the methods tested. This fact can be explained by the influence of other factors on productivity because good nutritional conditions do not necessarily reflect in high yields.…”
Section: Nbim Of the Sugarcane Crops By The Dris And Cnd Methods And mentioning
confidence: 66%
“…To calculate the functions of nutrient ratios some methods are adopted: a) the original method proposed by Beaufils (Beaufils, 1973); b) the Jones method (Jones, 1981); c) the method of Elwali and Gasho (Elwali & Gasho, 1984). According to Mourão Filho, Azevedo, and Nick (2002) there is no clear definition of what would be the best recommendation for calculating DRIS functions.…”
Section: Introductionmentioning
confidence: 99%
“…Para análise química do tecido vegetal se coletaram, em cada uma das plantas, as terceiras e quartas folhas de ramos vegetativos de cada um dos quadrantes da planta, conforme Mourao Filho et al (2002). Os macronutrientes (N, P, K, Ca e Mg) e micronutrientes (Zn e B) das folhas foram analisados conforme metodologia de Bataglia et al (1983).…”
Section: Methodsunclassified